Role of Sea Grant in Establishing Commercial Oyster Aquaculture through Applied Research and Extension. (30th December 2021) - Walton, William C.; Swann, LaDon
Abstract: Sea Grant programs, both separately and in collaboration, have supported growth of the off‐bottom oyster industry in all five U.S. states in the Gulf of Mexico. Here, we review the history of the Mississippi‐Alabama Sea Grant Consortium (MASGC) investments in research and extension to support the growth of this industry (particularly in Alabama and Mississippi). Notably, the integration of applied research with strategic extension efforts was essential to the success of this industry. The MASGC enabled the establishment of commercial off‐bottom oyster aquaculture in Alabama and Mississippi using a series of strategic, outcomes‐focused investments in applied research and extension efforts through an array of partnerships. In Alabama, the first commercial off‐bottom oyster farm was established in 2009. The industry grew to 22 farms by 2020 with a farmgate value of nearly 1.5 million, employing over 30 full time equivalents (FTE). Over 12 farms have been established in Mississippi in the last two years. The MASGC also leveraged additional support from other funding agencies that has multiplied the outcomes and impacts.